The Cyprus coastal heritage landscapes within Marine Spatial Planning process - Agapiou, Athos; Lysandrou, Vasiliki; Hadjimitsis, Diofantos G. (My University, 2017)
In many cases, antiquities are threatened due to the lack of a spatial planning that takes into consideration the sensitivity of these sites. As with in land sites, spatial planning is needed for coastal and sea sites too, in order to design current and future activities. The recently (2014) adopted Marine Spatial Planning directive (Directive 2014/89/EU) will be implemented – for the first time – by all EU member states by 2020. The specific goal of this directive is to establish a framework for maritime spatial planning (MSP) aiming to foster coordinated and coherent decision-making, to maximize the sustainable development, economic growth and social cohesion. For these tasks, MSP should take into consideration the protection of cultural heritage (both underwater and coastal) as well to intensify integrated planning for coastal areas. In addition, the European marine region of Mediterranean Sea adheres the Barcelona Convention for the Protection of the Marine Environment and the Coastal Region of the Mediterranean adopted in 1995, with Cyprus being one of the 22 Contracting Parties. MSP can be extremely complicated since a variety of activities need to be planned keeping at the same time a balance from one hand between the ecosystem, cultural and natural Heritage and on the other economic growth. Within this framework, the present paper discusses the assessment and evaluation of Marine Spatial Planning (MSP) related to the pressures to historical and archaeological coastal sites in Cyprus, using Geographical Information Systems (GIS). As evidenced from the present study, MSP is an efficient strategic way for protecting known CH sites, as well as for future prevention and safeguarding of either known or unknown (i.e. unexcavated) sites, by reallocating various activities potentially threatening CH monuments and landscapes, both marine and littoral.
Keywords: Conflicts; Cultural heritage protection; Cyprus; Geographical Information Systems; Marine spatial planning